New data on fauna and distribution of the tribe Cerambycini (Coleoptera: Cerambycidae) in Philippines - Barševskis, Arvīds; Torrejos, Chrestine (Baltic Journal of Coleopterology, 2024)
This article presents new information on the distribution of twenty-six species of longhorn beetles from the tribe Cerambycini (Coleoptera: Cerambycidae: Cerambycinae) in the Philippines. Fifteen of the species listed in this paper are known to be endemic in the archipelago. Eight new species occurrences were recorded in different islands with an addition of one species documented for the first time since its description.